Atomic-scale study of He ion irradiation-induced clustering in α-Zirconium. (1st January 2023) - Zhu, Hanliang; Qin, Mengjun; Wei, Tao; Davis, Joel; Ionescu, Mihail
ABSTRACT: Zircaloy-4 alloy specimens consisting of α-Zr grains were irradiated on a tandem accelerator with 5 MeV He ions to a fluence of 5 × 10 21 ions m   −   2 at different temperatures. Defect clusters and He bubbles were observed in the TEM micrographs of the irradiated microstructure. The small defect clusters and He bubbles were found to exhibit spherical shapes whereas the large defect clusters showed plate-like shapes. Molecular dynamics simulations and crystallography analyses revealed that the defect clusters are mainly composed of Zr interstitials. During He-ion irradiation, the clustering of Zr dumbbell interstitials results in the formation of small and spherical defect clusters. With further irradiation, the Zr interstitials prefer to occupy the octahedral sites that align along the { 1 2 ¯ 14 } planes with other site interstitials, forming cluster sections. These initial planar clusters then grow by extending along the < 10 1 ¯ 0 > directions and by forming more cluster sections along the < 1 2 ¯ 16 > directions, leading to large plate-like defect clusters on the { 1 ¯ 2 1 ¯ 1 } planes. He bubbles nucleate by the clustering of He atoms and vacancies that are formed by kicking out the lattice atoms, and then grow by the migration and coalescence of helium-vacancy clusters. Small He atoms have many interstitial sites to occupy in the α-Zr HCP crystal, allowing He bubbles to grow to spherical shapes. In addition, grain boundaries induce the accumulation of primary point defects and He atoms and high irradiation temperature accelerates diffusion, and hence larger defect clusters and He bubbles form in the grain boundary regions and at higher irradiation temperature. Graphical abstract: Image, graphical abstract